Impact of Moringa applications on growth attributes and oil content of Lemongrass plant - Hind M. Ibrahim; Tagelsir I.M. Idris (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
This study aimed to investigate the impact of Moringa applications on the growth attributes and oil content of Lemongrass plant under nursery conditions at Khartoum, Sudan. Moringa at: 0, 4, 8, 12 and 16 g/plant was tested as soil dressing, while the cold water extracts of dry leaves of Moringa were tested as foliar applications in concentrations: 0, 4, 8, 12 and 16 g/l. The tests were arranged in complete randomized design where each treatment was replicated six times. Data were collected six months after treatments. Considerable gains in growth parameters and leaves oil content were obtained upon soil dressing with 4 g of Moringa leaves per plant whereas these parameters were enhanced substantially by the 8 g/l foliar treatment. Further confirmatory tests are needed coupled with phyto-chemical studies to define the active constituents responsible for these enhancements.